Penerapan Konsep Manajerial Guru PAI Dalam Membentuk Kecerdasan Spiritual Siswa - Susanda Febriani; Junaidi; Supriadi; Akhyar, Muaddyl (Kariman: Jurnal Pendidikan Keislaman, 2024)
The position of teachers in the world of teaching is very important. Teachers are the determining factor for the success of quality learning. Teachers as managers have the task of managing time and classroom conditions from the initial activities to the end of learning. Comfort for students while in class is important to find formulations for teachers according to the objectivity of their students. So before the learning process takes place, the teacher manages the class properly. Here the teacher is required to be sensitive to the condition of the classroom and find the character of students. The problem found at SMPN 4 Bukittinggi is how to shape the spiritual intelligence of students through the application of the managerial concept of PAI teachers. The research method uses descriptive qualitative method. The result of this study is that SMPN 4 Bukittinggi City in shaping students' spiritual intelligence conducts religious activities including conditioning Islamic schools, teachers as role models for students, and teachers help students to formulate life missions. And also by following several ways exemplified by the Prophet in terms of learning activities.